Capital Charges under Basel II: Corporate Credit Risk Modelling and the Macro Economy - Kenneth Carling; Tor Jacobson; Jesper Lindé; Kasper Roszbach (Sveriges Riksbank, 2002)
The Internal Ratings Based (IRB) approach for capital determination is one of the cornerstones in the proposed revision of the Basel Committee rules for bank regulation. We evaluate the IRB approach using historical business loan portfolio data from a major Swedish bank for the period 1994 to 2000. First, we estimate a duration model that takes into account both company, loan related and macroeconomic variables. Next, we obtain a Value-at-Risktype (VaR) credit risk measure, by model-based simulations. Moreover, we study how both the banks credit risk and bu.er capital changes over time (had the bank been subject to the proposed rules). This approach allows us to (i) make individual forecasts of default risk conditional on company, loan and macro variables, (ii) study portfolio credit risk over time, (iii) assess to what extent the new Accord will achieve its main objective of increasing credit risk sensitivity in minimal capital charges, and (iv) compare current capital requirements to those under the proposed system. Our results show that macro conditions have great explanatory power in predicting default risk and calculating credit risk. The IRB approach, although sensitive to the choice of some horizon parameters, is an achievement in the intended direction.
Keywords: C41; G21; G33; G38; 330; Internal Ratings Based approach; relative risk weights; Value-at-Risk; credit risk models